Aplicação da gestão de processos em uma universidade pública do estado de São Paulo - Rodrigues, Gustavo de Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The business Process Management (BPM) is one of the current issues in the information age, because on the one hand, it addresses the interaction of people and organizations and on the other, recognition software processes. BPM unites business management of organizations to use methods, techniques and modeling tools, publication, control and analysis of business processes involving people and different systems. This work presents a literature review of processes, business processes, management of business processes, management of business processes, management of business processes in public organizations, structuring and process modeling, business process maturity and the major languages and tools for modeling business processes in order to see how BPM can help improve the processes of a Public University of São Paulo State, in addition to identifying and limiting potential barriers to the use of BPM in this context. For this, the comparision of some languages of process modeling and some modeling software processes to identify the best tools for the development modeling and some modeling software processes to identify the best tools for the develpment of this work was performed. After, we proceeded with the implementation of the BPM lifecycle management, through the stages of planning, modeling and optimization and implementation of processes. Besides the benefits of application of BPM, such as reduced time and processes running costs, increased knowledge about the process, bureaucracy reduction for its implementation and automation of processes through the development of a management software processes were found limitations for its implementation, such as the organizational structure of a public university, the number and complexity of cases, the level of maturity in which the proceedings are, cultural issues and resource constraints for acquisition of suitable tools for deploying BPM

O Business Process Management (BPM) é considerado por alguns autores um dos temas mais atuais na era da informação, pois, de um lado, ele aborda a interação de pessoas e organizações e, de outro, softwares de reconhecimento de processos. O BPM une gestão de negócio e tecnologia da informação promovendo a interação e melhoria dos processos de negócio das organizações ao utilizar métodos, técnicas e ferramentas de modelagem, publicação, controle e análise de processos operacionais envolvendo pessoas e sistemas diversos. Neste trabalho é apresentada uma revisão bibliográfica sobre processos, processos de negócio, gestão de processos de negócio, gestão de processos de negócio em organizações públicas, estruturação e modelagem de processo, maturidade em processos de negócios e principais linguagens e ferramentas para modelagem de processos de negócio. O objetivo deste trabalho foi verificar como o BPM pode auxiliar na melhoria dos processos de uma Universidade Pública do Estado de São Paulo, além de identificar potenciais limitantes a entraves ao uso do BPM neste contexto. Para isso, foi realizada a comparação de algumas linguagens de modelagem de processos e de alguns softwares de modelagem de processos de modo a identificar as melhores ferramentas para o desenvolvimento deste trabalho. Após, procedeu-se com a aplicação do ciclo de gerenciamento de BPM, passando pelas etapas de planejamento, modelagem e otimização e implantação dos processos. Além dos benefícios da aplicação do BPM, como redução de tempo e custos de execução dos processos, o aumento do conhecimento, sobre o processo, a redução de burocracia para sua execução e automação dos processos através do desenvolvimento de um software de gerenciamento dos processos, foram encontradas limitações para sua implantação, como a estrutura organizacional de uma Universidade Pública, o número e a complexidade dos processos, o...
Keywords: Processos de fabricação; Administração; Universidades e faculdades; Administração pública; Manufacturing processes